High-resolution Mass Spectrometry Analysis of Plant-derived Components of Amrytavir Liquid having Antibiotic Effect Through Antimicrobial Activity and Anticovid Activity by the Ultra-highperformance Liquid Chromatography-Based System and its Pharmac - Prof. K. Ramachandra Reddy, (Asian Journal of Pharmaceutics (AJP), 2025)
The Amrytavir liquid is prepared by different plant extracts by Ayurvedic manufacturing procedure among the ingredients of Amrytavir liquid such as Withania somnifera, Emblica officinalis, Nigella sativa, Oroxylum indicum, Gmelina arborea, Uraria picta, Solanum virginianum, Cuminum cyminum, Mesua ferrea, Cyperus rotundus, Vitis vinifera, and Cinnamomum verum are major plant extracts showing antibiotic effect through antimicrobial activity which revealed by the high-resolution mass spectrometry analysis of Amritavir Liquid. The listed antibiotic compounds identified are Nitecapone, Reductiomycin, Terbufos, Dimethylthionine, Corydaline, Lahorenoic acid A, Trifloxystrobin, Pyrimethamine, Xanthoangelol C, Hydranthomycin, Penialidin C, Hapalindole O, Duloxetine, Nybomycin, Asperglaucide, Lasiodipline A, Xiamycin E, and Bucillamine. Literature reports have documented that these compounds show antimicrobial and anticovid effects. The pharmacokinetic study revealed that most of the compounds are water soluble which facilitates easy administration. It is also revealed that most of the antibiotic compounds show high intestinal absorption which facilitates rapid drug action over the human body system.